Business environment and strategies of wood industry companies in Leningrad and Vologda regions results from a pilot study - Toppinen, Anne; Toivonen, Ritva; Järvinen, Erno; Goltsev, Vadim; Tatti, Natalia; Mutanen, Antti (Finnish Forest Research Institute, 2007)
This pilot study examines resources and capabilities and their utilisation to support business and marketing strategies in the case of small/medium-sized wood industry companies in the Leningrad and Vologda regions. An increasing body of literature emphasises the strategic choices of core competencies/capabilities based on resources and the combination of these with marketing strategies. Both competencies and capabilities need to be aligned to the business environment where the company operates. The realisation of the potential that resources and capabilities provide as actual competitive advantages was studied based on managers perceptions on their companies market position. Furthermore, the competitive advantages at the market place were analysed against the competitive environment where the companies operate, and their decisions of the current and future geographical location. The data consists of personal interviews of managers in 12 wood industry case companies operating in Leningrad region and 6 companies in Vologda region. The interviews were conducted between May 2005 and January 2006.The interviewed managers of Russian woodworking companies emphasised closeness to the markets, good logistic connections and large market size as the main sources of their competitive advantage. Forest resources and availability of wood raw material or price of wood raw material were not considered as particularly significant sources of competitive advantage. The overall reliability, good image and reputation of the company and its qualified and skilled personnel were the most important factors in which the interviewed managers of case companies estimated to be in the best competitive position against their rivals. In profit margins, in market share, and in networking with other companies producing similar products, the respondents perceived to be in the weakest competitive position in comparison to their competitors. High taxation, corruption and lack of capital strongly characterised the problems present in their business environment. In the future, these case companies wanted to change from commodity products towards more specialised products, and focus more on export markets in Europe than the domestic markets. If the results are more generalisable, competition in the European markets for wood products will intensify, extending also to the markets for higher value added wood products.
Published jointly with Pellervo Economic Research Institute
Keywords: Venäjä; kilpailustrategiat; puutuoteteollisuus; competitive advantage; competitive positioning; environmental quality; Northwest Russia; resources; wood products industry